Anti-plague service in the fight against infectious diseases (historical review of the 90th anniversary of the Rostov-on-Don Anti-Plague Institute of Rospotrebnadzor) - N. E. Gaevskaya; E. I. Markovskaya; V. V. Agafonova (Медицинский вестник Юга России, 2025)
Objective: on the contribution of anti-plague institutions to ensuring the sanitary and epidemiological well-being of the country's population. Materials and methods: an analytical review of information from literary sources and databases of Cyberlenink electronic libraries, e-library, as well as archival materials and the library fund of the Institute. Results: the causes and ways of the emergence of the anti-plague system in Russia (hereinafter referred to as the anti-plague service) are outlined, the evolutionary stages of formation are shown, during which the search for the most effective and optimal forms of organiza tion aimed at ensuring a safe epidemiological situation in Russia was carried out. Conclusion: the article contains an assessment of the importance of the work of the Rostov-on-Don Scientific Research Anti-Plague Institute. The main tasks for ensuring pre paredness in case of epidemic complications in Russia are outlined.